The Existence of Independent Palm Oil Plantations on The Socio-Economic Conditions of The Sungai Aur District Community West Pasaman District - Rambe, Khoirul Amri; Fitrisia, Azmi; Iskarni, Paus (Economic: Journal Economic and Business, 2025)
This study aims to determine the socio-economic conditions of the Sungai Aur District community, the majority of whose population relies on independent oil palm plantations as their main source of livelihood. The approach used is descriptive qualitative, with a primary focus on aspects such as the level of education in the family, the health of family members, and the income of the head of the family. The data collected consists of primary and secondary data, with sources of information coming from informants who have competence in their fields, including the Jorong Head and staff related to the research issue, the principal, several teachers, and local community leaders. Data collection methods include direct observation, in-depth interviews, and documentation. Data analysis was carried out using an interactive model developed by Miles and Huberman.